2000
DOI: 10.1046/j.1439-0434.2000.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Some Coffea arabica Genotypes to Strains of Colletotrichum kahawae, the Cause of Coffee Berry Disease

Abstract: Pathogenicity tests were performed on 11 genotypes of Coffea arabica using single‐isolate suspensions of Colletotrichum Kahawae obtained from 90 monoconidial isolates. The objective of this study was to estimate the proportion of pathogenic variation corresponding 10 differences in aggressiveness and virulence (races). A large part of the variation in the pathogen population was due to aggressiveness. The differential effects were too small to suggest conclusively that races exist. This paper discusses the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…In more exhaustive studies differences were only found in the aggressiveness in C. kahawae isolates (Manga et al, 1998). Omondi et al (1997Omondi et al ( , 2000 working with local Kenyan isolates concluded that variation in pathogenicity among isolates of C. kahawae was predominantly due to aggressiveness, and differential pathogenicity, although small, was highly significant and could not be ignored. However they did not find positive evidence of physiologic races for C. kahawae.…”
Section: Fungal Variabilitymentioning
confidence: 99%
“…In more exhaustive studies differences were only found in the aggressiveness in C. kahawae isolates (Manga et al, 1998). Omondi et al (1997Omondi et al ( , 2000 working with local Kenyan isolates concluded that variation in pathogenicity among isolates of C. kahawae was predominantly due to aggressiveness, and differential pathogenicity, although small, was highly significant and could not be ignored. However they did not find positive evidence of physiologic races for C. kahawae.…”
Section: Fungal Variabilitymentioning
confidence: 99%
“…Studies done previously on C. arabica genotypes variety x C. kahawae strains reported existence of interaction, but found to be less significant to suggest conclusively that differential interaction exists (Omondi et al, 2000).…”
Section: Discussionmentioning
confidence: 69%
“…The divergence of HDT derivatives is also of importance in breeding programmes. For example, Ruiru 11 progenies comprise of 60 lines (Omondi et al, 2001) and therefore more intensive molecular analysis could help in characterizing them and consequently selecting elite lines.…”
Section: Discussionmentioning
confidence: 99%